2019
DOI: 10.1007/s10461-019-02413-y
|View full text |Cite
|
Sign up to set email alerts
|

High HIV/STI Test Acceptance Through a Behavioral Health Encounter in Latino Immigrants with Substance Use and Mental Health Problems

Abstract: Latino immigrants with substance use and mental health problems are at risk for undiagnosed HIV and sexually transmitted infections (STIs). Participants in a randomized control trial were recruited in Boston, USA and Madrid and Barcelona, Spain. Eligibility criteria were Latino self-identification, age 18-70, elevated substance use and mental health symptoms, and not currently in substance or mental health care. A multinomial logistic regression examined predictors of HIV/STI testing decline and lost to follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…and "Do you ever feel bad or guilty about your drug use?" The previous research has found adequate internal consistency (α = .87) with a Latino immigrant sample (Levison et al, 2019). The scale demonstrated adequate internal consistency in the present study (α = .86).…”
Section: Drug Use Severitysupporting
confidence: 61%
See 1 more Smart Citation
“…and "Do you ever feel bad or guilty about your drug use?" The previous research has found adequate internal consistency (α = .87) with a Latino immigrant sample (Levison et al, 2019). The scale demonstrated adequate internal consistency in the present study (α = .86).…”
Section: Drug Use Severitysupporting
confidence: 61%
“…The Drug Abuse Screen Test (Yudko et al, 2007) was used to measure drug use severity. Participants were asked to respond “yes” or “no” to the 10-item self-report scale that inquired about a variety of behaviors related to drug use severity such as “Are you always able to stop using drugs when you want to?” and “Do you ever feel bad or guilty about your drug use?” The previous research has found adequate internal consistency (α = .87) with a Latino immigrant sample (Levison et al, 2019). The scale demonstrated adequate internal consistency in the present study (α = .86).…”
Section: Methodsmentioning
confidence: 90%
“…Response scores include “Yes” or “No” to items that include, “Are you always able to stop using drugs when you want to?” and “Does your spouse (or parents) ever complain about your involvement with drugs?” Sum of scores were calculated to reflect past-year drug use, where higher scores indicated higher use (ranging from 0 to 10). Previous research has found adequate internal consistency (α = .87) with a Latino immigrant sample (Levison et al, 2019). In the present study, inter item reliability was good (full sample: α = .88; SML adult sample: α = .89; non-SML sample: α = .88).…”
Section: Methodsmentioning
confidence: 91%